Effect of Interfacial Engineering in Solid‐State Nanostructured Sb2S3 Heterojunction Solar Cells. Issue 1 (18th September 2012) - Fukumoto, Takafumi; Moehl, Thomas; Niwa, Yusuke; Nazeeruddin, Md. K.; Grätzel, Michael; Etgar, Lioz
<x xml:space="preserve">Abstract</x> Surface treatment by decyl‐phosphonic acid (DPA) reduces the recombination and increases the open circuit voltage and the fill factor of the inorganic–organic Sb2S3 hetrojunction solar cell. It is revealed that the DPA attaches to both surfaces, the uncovered TiO2 surface and the Sb2S3 surface. This cell produces a power conversion efficiency of 3.9% under 1 sun intensity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>